Assessing the Value of U.S. Army International Activities - Marquis, Jefferson P.; Darilek, Richard E.; Castillo, Jasen J.; Thurston, Cathryn Quantic; Wong, Anny (RAND Corporation, 2023)
This report presents a framework for assessing U.S. Army International Activities (AIA). It also provides a matrix of eight AIA "ends," derived from top-level national and Army guidance, and eight AIA "ways," which summarize the various capabilities inherent in AIA programs. In addition, the report describes the new online AIA Knowledge Sharing System (AIAKSS) that is being used to solicit programmatic and assessment data from AIA officials in the Army's Major Commands.